Physical Methods in Bioinorganic Chemistry : Spectroscopy and Magnetism - Que, Lawrence (Sausalito : University Science Books, 2000)
This text provides detailed coverage of physical methods used in bioinorganic chemistry. Individual chapters are devoted to electronic absorption spectroscopy, resonance Raman spectroscopy, electron paramagnetic resonance spectroscopy, ENDOR and ESEEM, magnetic circular dichroism, Mössbauer spectroscopy, magnetism, NMR spectroscopy as applied to paramagnetic systems, and x-ray absorption spectroscopy. The book aims to provide a fundamental understanding of each method and demonstrate how data obtained from a system of bioinorganic interest can be interpreted. Case studies are presented in the last chapter in which more than one technique has been applied to gain insight into each given bioinorganic problem. By integrating theory with experimentation and providing an orientation that is more biological than that presented in previously published books, Physical Methods in Bioinorganic Chemistry: Spectroscopy and Magnetism will serve as an important new text for students of bioinorganic chemistry, biochemistry, molecular biology, and their professors.
Includes appendix and index
Keywords: Bioinorganic chemistry; Spectroscopy; Magnetism; Analytical chemistry